Facile synthesis of nitrogen and fluorine doped 3-dimensional reduced graphene oxide electrode for the removal of copper ions by capacitive deionization - Mamaril, Gil Stefan S.; De Luna, Mark Daniel G.; Doong, Ruey-An (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
This study focused on a facile synthesis of Nitrogen- and Fluorine- doped 3 Dimensional Reduced Graphene Oxide (NFrGO) electrode for the removal of copper ions from aqueous solution by Capacitive Deionization (CDI). The time of reaction varies to determine the optimum time for the hydrothermal synthesis of NFrGO to achieve a porous material. The BET surface area of NFrGO that was synthesized using 16 hours as the reaction time (16-h) is 182.74 m2 g-1, and its average pore size is 10.34 nm. The electrochemical performance of the as-prepared material shows a large area for cyclic voltammogram, resulting to a high specific capacitance of 245.6 F g-1. A 16-h was used as the electrode to remove copper ions in aqueous solution. The synthesized - porous material gave a high percent removal of 94.48%, and a specific electrosorption capacity of 52.38 mg g-1 using 100 mg L-1 Cu(II) as the initial concentration. The removal of copper ions can be modelled using pseudo 2nd order adsorption kinetic and intraparticle diffusion. Results showed that Nitrogen- and Fluorine- doped 3-Dimensional Reduced Graphene Oxide is a promising material that can effectively remove copper ions by capacitive deionization.
Thesis (Master of Science in Environmental Engineering)--University of the Philippines Diliman
Keywords: Sewage -- Purification -- Heavy metals removal; Capacitive deionization (CDI).